DIRECTIONS FOR IMPROVING PUBLIC ADMINISTRATION OF THE DEVELOPMENT OF TERRITORIES OF UKRAINE UNDER CURRENT CONDITIONS - Yasenchuk, Roman (Global Prosperity, 2025)
The theoretical and methodological principles of state management of territorial development are substantiated. The scientific understanding of territorial development as a complex process aimed not only at economic growth, but also at ensuring the functional balance, viability, and long-term capacity of territories in an unstable environment is clarified. The theoretical provisions of ensuring the stability, adaptability, and security of territories as a methodological basis of modern state regional policy are substantiated. It is proved that the mentioned categories are not isolated characteristics of territorial development, but form a single conceptual framework within which the territory appears as a system capable of maintaining critical functions, counteracting external shocks, adapting to new conditions and moving towards restoration and modernization. The current state of regulatory, institutional and organizational support for state management of territorial development in Ukraine is analyzed, which made it possible to identify key structural imbalances and functional limitations of the current system. It was found that, despite the updating of the legislative framework, the development of decentralization, the expansion of the powers of territorial communities and the introduction of strategic planning, the territorial development management system continues to be characterized by uneven community capacity, insufficient coordination between levels of public authority, weak integration of strategic and budgetary decisions and limited readiness to function in conditions of external threats. A comprehensive assessment of the impact of external challenges and threats on the development of the territories of Ukraine was carried out, which allowed us to establish their multidimensional, systemic, and spatially differentiated nature. It is shown that military, demographic, economic, humanitarian, environmental and security factors not only increase interregional disparities, but also change the functional load of individual communities and regions, transform the structure of local economies, deepen infrastructural vulnerability and reduce the level of financial and institutional stability. The priorities for improving the mechanisms of state management of territorial development in Ukraine have been substantiated and scientific and practical recommendations for their implementation in the regulatory, institutional, strategic, financial and economic, digital, security and partnership dimensions have been developed. It has been proven that only a comprehensive combination of these areas creates the appropriate prerequisites for the formation of an adaptive, sustainable, security-oriented and effective system of state management of territorial development.